Short-Term Surgical Complications of Skin-Sparing Mastectomy and Direct-to-Implant Immediate Breast Reconstruction in Women Concurrently Treated with Adjuvant Radiotherapy for Breast Cancer - Kooijman, Merel M. L.; Hage, J. Joris; Scholten, Astrid N.; Vrancken Peeters, Marie-Jeanne T. F. D.; Woerdeman, Leonie A. E. (Archives of Plastic Surgery, 2022)
Background Postmastectomy radiotherapy (PMRT) is allegedly associated with a higher risk of complications of combined nipple-sparing or skin-sparing mastectomy and subpectoral direct-to-implant immediate breast reconstruction ([N]SSM/SDTI-IBR). For this reason, this combination is usually advised against or, even, refused in women who need to undergo PMRT. Because this advice has never been justified, we assessed the short-term complications that may potentially be associated with PMRT after [N]SSM/SDTI-IBR.Methods We compared the complications requiring reintervention and implant loss occurring after 273 [N]SSM/SDTI-IBR that were exposed to PMRT within the first 16 postoperative weeks (interventional group) to those occurring in 739 similarly operated breasts that were not (control group). Additionally, we compared the fraction of complications requiring reintervention occurring after the onset of radiotherapy in the interventional group to that occurring after a comparable postoperative period in the control group.Results The fraction of breasts requiring unscheduled surgical reinterventions for complications and the loss of implants did not differ significantly between both groups but significantly more reinterventions were needed among the controls (p = 0.00). The fraction of events after the onset of radiotherapy in the interventional group was higher than the fraction of events after 6.2 weeks in the control group, but not significantly so.Conclusion We found no prove for the alleged increase of short-term complications of adjuvant radiotherapy. Therefore, we advise that these should not be considered valid arguments to advice against [N]SSM/SDTI-IBR.
Keywords: breast reconstruction; breast implant; radiotherapy